COMMUNITY-BASED EVALUATION OF PUBLIC HEALTH POLICY IMPLEMENTATION IN RURAL AREAS - Asni Hasanuddin; Auliyah Imtiyaz Putri Mentari (JOURNAL OF COMMUNITY DEDICATION, 2026)
This study aims to analyze the implementation of public health policies in rural areas through a community-based approach using a literature review method. The primary focus of the study is to evaluate the extent to which government-designed health policies are effectively implemented at the local community level, as well as the role of communities in supporting or hindering their success. The method used is a systematic literature review of various scientific sources, such as international journals, policy reports, and recent publications from relevant health organizations. The study results indicate that the success of health policy implementation in rural areas is significantly influenced by active community participation, the availability of health resources, the capacity of health workers, and the policy's suitability to local socio-cultural conditions. Furthermore, a community-based approach has been shown to increase the effectiveness of health programs through community empowerment, increased health awareness, and strengthened participatory evaluation mechanisms. However, various challenges remain, such as limited infrastructure, low health literacy, and lack of coordination among stakeholders. This study recommends the importance of integrating community perspectives into every stage of policymaking, from planning to evaluation, to create a more inclusive and sustainable health system in rural areas.